Characterization of large deletions of the MECP2 gene in Rett syndrome patients by gene dosage analysis - Silvia Vidal; Ainhoa Pascual‐Alonso; Marc Rabaza‐Gairí; Edgar Gerotina; Nuria Brandi; Paola Pacheco; Clara Xiol; Mercè Pineda; Rett Working Group; Judith Armstrong (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background Rett syndrome (RTT) is a developmental disorder with an early onset and X‐linked dominant inheritance pattern. It is first recognized in infancy and is seen almost always in girls, but it may be seen in boys on rare occasions. Typical RTT is caused by de novo mutations of the gene MECP2 (OMIM*300005), and atypical forms of RTT can be caused by mutations of the CDKL5 (OMIM*300203) and FOXG1 (OMIM*164874) genes. Methods Approximately 5% of the mutations detected in MECP2 are large rearrangements that range from exons to the entire gene. Here, we have characterized the deletions detected by multiplex ligation‐dependent probe amplification (MLPA) in the gene MECP2 of 21 RTT patients. Breakpoints were delineated by DNA‐qPCR until the amplification of the deleted allele by long‐PCR was possible. Results This methodology enabled us to characterize deletions ranging from 1,235 bp to 85 kb, confirming the partial or total deletion of the MECP2 gene in all these patients. Additionally, our cases support the evidence claiming that most of these breakpoints occur in some restricted regions of the MECP2 gene. Conclusion These molecular data together with the clinical information enable us to propose a genotype–phenotype correlation, which is essential for providing genetic counseling.